The Role of Political Freedoms in Gender Inequalities: Global Evidence - Mehdi Hajamini; Ameneh Zare; Abolfazl Dehghani; Masoud Nikooghadam (زن در توسعه و سیاست)
In today’s world, the socio-economic statuses of women and men have evolved; however, the effects of masculine ideologies are still evident, particularly in developing and underdeveloped countries. The function of governments as a shield that protects the interests of men is widely believed to be historically and institutionally related to this inequality of opportunities. As a result, the present paper has investigated the role of political structure and power on gender inequalities using two methods of variance analysis and random forest, as well as over 2500 observations from 94 countries between 1970 and 2020. For this purpose, Hofstede’s cultural dimensions and political rights and civil liberties indicators were implemented. Based on the variance analysis, two dimensions of democratic political structure were found to be significantly involved in the explanation of the disparity between gender development and gender inequality, particularly the primary difference between not-free and partly-free countries and free countries. In order to experience a society with minimal gender discrimination, it is imperative to prioritize civil liberties and political rights, as the random forest results also confirmed. However, the results concerning cultural characteristics are exceedingly susceptible to fluctuations and are contingent upon the sample or gender index . A policy trade-off between gender freedom and development is not presented to policymakers in developing and underdeveloped countries; rather, they are presented with an all-or-nothing choice. Reducing gender inequality and achieving a free political system are two aspects of the same coin.